2010
DOI: 10.4103/0972-0707.66718
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning and shaping the root canal with an Nd: YAG laser beam: A comparative study

Abstract: Aim:This study was undertaken to evaluate the effectiveness of an experimental Nd:YAG laser fiberoptic delivery system compared with conventional methods for its ability to cleanse and shape the root canal space in vitro.Materials and Methods:Thirty-two teeth were divided into two groups. In the first group, the canals were instrumented with k files, in the second the initial preparation was done with a K file and completed with a laser beam.Results:Scanning electron microscopic evaluations showed that prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Various types of lasers have been extensively studied in root canal treatments. Lasers have been investigated for their suitability in the preparation [18][19][20][21][22] and disinfection of the root canal [23][24][25] and in the removal of gutta-percha [26][27][28], but their usefulness for root canal filling has been investigated infrequently [16,29,30]. Maden et al [29] compared conventional lateral condensation, Nd:YAG lasersoftened gutta-percha, and the continuous wave of condensation technique using System B HeatSource to determine which caused the least apical leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of lasers have been extensively studied in root canal treatments. Lasers have been investigated for their suitability in the preparation [18][19][20][21][22] and disinfection of the root canal [23][24][25] and in the removal of gutta-percha [26][27][28], but their usefulness for root canal filling has been investigated infrequently [16,29,30]. Maden et al [29] compared conventional lateral condensation, Nd:YAG lasersoftened gutta-percha, and the continuous wave of condensation technique using System B HeatSource to determine which caused the least apical leakage.…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary objectives of root canal therapy is cleaning of the canal system to eliminate tissue debris and microorganisms (Moogi & Rao, 2010). Studies have indicated that chemico-mechanical instrumentation in combination with canal irrigation cannot completely remove debris from the root canal system.…”
Section: Discussionmentioning
confidence: 99%
“…Moogi & Rao (2010) used SEM to compare the effectiveness of an experimental Nd:YAG laser fiber optic delivery system with conventional methods to clean and shape the root canal space. Results indicated that the laser beam improves the cleanliness of canal walls in comparison with conventional techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleansing and shaping of the root canal system, followed by adequate obturation are the major objectives of endodontic treatment. [ 1 ] Root canal obturation provides a seal that prevents microleakage and subsequent reinfection of the canal and the periradicular tissues. [ 2 ] For this reason, different endodontic materials and obturation techniques have been applied for decreasing microleakage and improvement of seal.…”
Section: Introductionmentioning
confidence: 99%